Diseño de una planta piloto para la elaboración de productos cítricos en la Parroquia el Paraíso del cantón Las Lajas. - Chimarro García, Cristopher V. (2015)
The work is the design of a pilot plant in the parish Paradise, which is a producer of citrus fruits like orange, lemon and mandarin. However, farmers suffer heavy losses because currently there are no other routes of different harvesting fresh market, for domestic consumption or for sale to middlemen, but much of the production of these fruits are impaired in plants because the producer is not profitable to harvest in full fruit, this is because they do not get a sustainable income from the sale of the fruit. Thus, there is a large volume of processed fruits susceptible to give rise to several products including juices have to take advantage of these agricultural products, aiming to give added value.